Diversity and groups (Research on managing groups and teams, 2008)
Demographic faultlines and creativity in diverse groups / Lisa H. Nishii, Jack A. Goncalo -- Metaperceptions in diverse work groups : intrapersonal perspectives and intragroup processes / Eden B. King, Seth Kaplan, Steve Zaccaro -- Self-disclosure : beneficial for cohesion in demographically diverse work groups? / Tracy L. Dumas, Nancy P. Rothbard, Katherine W. Phillips -- To be enhanced, understood, distinct, or to belong? : the role of multiple identity motives in homogeneous and diverse groups / Margaret E. Ormiston, Elaine M. Wong -- Beyond information exchange : new perspectives on the benefits of racial diversity for group performance / Samuel R. Sommers -- Diversity, newcomers, and team innovation : the importance of a common identity / Floor Rink, Naomi Ellemers -- Harnessing the power of emergent interdependence to promote diverse team collaboration / Heather M. Caruso, Anita Williams Woolley -- The language of bias : a linguistic approach to understanding intergroup relations / Quinetta M. Roberson, Bradford Bell, Shanette C. Porter -- A contextual reexamination of work team diversity research : review and future agenda / Aparna Joshi, Hyuntak Roh -- Capstone chapter for the volume : integrating themes and future research opportunities in work group diversity / Jennifer A. Chatman -- Taking advantage of differences : increasing team innovation through identity integration / Chi-Ying Cheng, Jeffrey Sanchez-Burks, Fiona Lee -- Duo status : disentangling the complex interactions within a minority of two / Denise Lewin Loyd, Judith B. White, Mary Kern -- In search of significance : a role-set approach to uncovering the social importance of demographic categories / Ray Reagans -- Preface / Katherine W. Phillips